Evidence of developmental escape from transcriptional gene silencing in MESSI retrotransposons - Sanchez, Diego Hernan (2019)
Transposable elements (TEs) are ubiquitous genomic features. ‘Copy-and-paste’ long-terminal-repeat (LTR) retrotransposons have been particularly successful during evolution of the plant kingdom, representing a substantial proportion of genomes. For survival in copious numbers, these TEs may have evolved replicative mobilization strategies that circumvented hosts’ epigenetic silencing. Stressful circumstances are known to trigger the majority of known mobilizing plant retrotransposons, leading to the idea that most are activated by environmental signals. However, previous research revealed that plant developmental programs include steps of silencing relaxation, suggesting that developmental signals may also be of importance for thriving parasitic elements. Here, we uncover an unusual family of giant LTR retrotransposons from the Solanum clade, named MESSI, with transcriptional competence in shoot apical meristems of tomato. Despite being recognized and targeted by the host epigenetic surveillance, this family is activated in specific meristematic areas fundamental for plant shoot development, which are involved in meristem formation and maintenance. Our work provides initial evidence that some retrotransposons may evolve developmentally associated escape strategies to overcome transcriptional gene silencing in vegetative tissues contributing to the host's next generation. This implies that not only environmental but also developmental signals could be exploited by selfish elements for survival within the plant kingdom